THE INPUT POWER FACTOR PROBLEM FOR INDUSTRIAL DRIVES - Osunde O.D; Makanjuola N.T (Academy Journal of Science and Engineering)
This paper presents the a.c. input power factor problem of an Industrial drive connected to a DC motor load and operated either in the continuous or discontinuous inductor current mode. This research became necessary in view of the Federal Government of Nigeria’s growing interest in the rail transport system and the likelihood of deploying Electric trains in the future. It begins with an in - depth mathematical analysis of the drive system and its performance factors such as: Harmonic factor (HF), Displacement factor (DF), Power factor (PF). The result shows the non – sinusoidal a.c input current in both the continuous and discontinuous current mode with high lower order harmonics.